Financial mechanisms of the economic component of forecasting and development of general secondary education in Ukraine - Klymchuk, Iryna (ScienceRise: Pedagogical Education, 2020)
The inefficiency of the current system of financing education in Ukraine in the conditions of budget deficit necessitates the search for / implementation of mechanisms that promote the development of economic independence of general education institutions to increase the efficiency of financial resources. The article presents an analysis and definition of regulatory costs of educational services in Ukraine, in particular: presents the calculation of regulatory costs of educational services in Ukraine and substantiates the need to develop stages of implementation of the program of transition of general secondary education to regulatory funding. Introduction of regulatory funding, development and coordination of the main stages of financing of educational institutions, taking into account regulatory funding, will lead to increase of quality of education, level of motivation and efficiency of work of school. In this regard, the application of foreign experience in reforming financial relations between the state and educational institutions, defining and developing the sequence of measures / stages of implementation of the program of transition to regulatory funding will help improve the mechanism of using budget funds. Determination of regulatory costs is based on the calculation of: the cost of providing educational services in the current and planning period / year. Accordingly, it should be an incentive for high performance of the school, based on the calculation of the integrated performance of educational institutions. The introduction of the normative principle of financing educational institutions requires the development of stages of transition to new principles of financing. In this regard, the sequence of measures / stages for the implementation of the program of transition of educational institutions to regulatory funding is defined and presented. The introduction of the main stages and measures of financing of general educational institutions will lead to the improvement of the quality of work of educational institutions